2004
DOI: 10.1165/rcmb.2003-0011oc
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymorphisms Influencing Transcription of the Human CHRM2 Gene in Airway Smooth Muscle

Abstract: The human muscarinic M 2 receptor is a functionally important membrane-bound protein that is negatively coupled to adenylyl cyclase and is widely expressed in a range of tissues, including cardiac myocytes, prejunctional cholinergic nerve endings, and smooth muscle. In the airways, M 2 receptors are constitutively expressed on airway smooth muscle (ASM) and, in contrast to muscarinic M 3 receptors, continue to be expressed during primary culture (1). Muscarinic M 2 receptors play an important role in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
5
36
1
2
Order By: Relevance
“…For both quantitative LightCycler PCRs and semiquantitative RT-PCRs, 1 g of total RNA was reversetranscribed into cDNA using an oligo (dT) 15 primer using the firststrand cDNA synthesis system. Amplification of cDNA was performed by quantitative PCR on the LightCycler using fast start Taq DNA polymerase containing the double-stranded DNA binding dye SYBR Green 1.…”
Section: Mrna Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For both quantitative LightCycler PCRs and semiquantitative RT-PCRs, 1 g of total RNA was reversetranscribed into cDNA using an oligo (dT) 15 primer using the firststrand cDNA synthesis system. Amplification of cDNA was performed by quantitative PCR on the LightCycler using fast start Taq DNA polymerase containing the double-stranded DNA binding dye SYBR Green 1.…”
Section: Mrna Analysismentioning
confidence: 99%
“…Preparation of promoter deletion constructs and reporter assay analysis Preparation of RNA, 5Ј Rapid Amplification of cDNA ends, cloning, and sequencing from IMR32 cells were performed as described previously in human airway smooth muscle cells (15). Regions upstream of each of the three identified major transcription start sites were investigated for promoter activity based on information obtained from the analysis of the 5ЈRACE results.…”
Section: Identification Of the Promoter Sequence Of The M 2 Muscarinimentioning
confidence: 99%
“…The level of expression of the M2 and M3 receptor in the airways is partly dependent upon transcriptional controlling mechanisms: both the CHRM2 and CHRM3 promoters have been defined and are known to contain a range of polymorphic variants [14,46]. The current authors have recently shown that different alleles of a dinucleotide repeat in the M2 promoter alter levels of reporter gene expression [14]: this may, therefore, result in altered M2 receptor expression in vivo. The effects of these polymorphisms on treatment response (if any) remain to be established.…”
Section: Muscarinic Receptorsmentioning
confidence: 88%
“…While this work is still in progress it is clear that there is at least as much genetic variability in regulatory regions governing transcription as in the coding regions of the target themselves. Less is known about the functional relevance of polymorphisms in these regulatory regions of DNA, although there is reasonable evidence supporting functional roles for polymorphisms in the promoter of the human b 2 -adrenoceptor [11][12][13] and the muscarinic M2 receptor [14].…”
Section: Variability In Key Airway Targetsmentioning
confidence: 99%
“…(Fenech, 2001). The expression of M2 and M3 receptors is dependent on transcription regulation in the gene promoter region and polymorphisms have been demonstrated in both promoter regions (Fenech, 2004;Donfack, 2003). Furthermore different expression of M2 receptor may be related to various number of dinucleotide CA repetitions in gene promoter region.…”
Section: Polymorphism Of Ac9 Gene (Cyclase Adenylate 9)mentioning
confidence: 99%